Sperm characteristics in normal and abnormal ejaculates are differently influenced by the length of ejaculatory abstinence. (13th July 2022) - Meitei, Huidrom Yaiphaba; Uppangala, Shubhashree; Lakshmi R, Vani; Guddattu, Vasudeva; Hegde, Padmaraj; Kumar, Pratap; Adiga, Prashanth; Kalthur, Guruprasad; Schlatt, Stefan; Adiga, Satish Kumar
Abstract: Background: No association between the length of ejaculatory abstinence (LEA) and semen characteristics has been confirmed. A short LEA has been linked to improved sperm characteristics and a higher pregnancy rate, but its negative influence on sperm chromatin maturity and longevity may adversely affect reproductive outcomes. Objectives: We sought to determine the influence of LEA on (i) semen parameters in normozoospermic and abnormal ejaculates; and (ii) the outcomes of sperm‐preparation methods in a large number of subfertile men undergoing infertility workups. Materials and methods: This retrospective registry‐based cohort study analyzed the data of 10, 674 ejaculates from 7972 subfertile men, who were then segregated into normozoospermic, oligozoospermic, asthenozoospermic, and oligo‐asthenozoospermic cohorts. Variations in semen characteristics and post‐wash outcomes were studied between four LEA intervals across 0–15 days. Results: An age‐adjusted analysis of covariance (ANCOVA) model linked significant increases in ejaculate volume, sperm concentration (except in the oligozoospermic cohort), and total sperm count to an increased LEA ( p  < 0.05). LEA was negatively associated with motility (except in the asthenozoospermic cohort) and vitality ( p  < 0.05). Large‐headed spermatozoa were less common with an increased LEA only in the oligo‐asthenozoospermic cohort ( p  < 0.05). In the normozoospermic cohort, a longer LEA led to fewer spermatozoa with amorphous heads but more spermatozoa with tapered heads and cytoplasmic droplets ( p  < 0.05). LEA extension resulted in greater sperm DNA fragmentation in the abnormal cohort ( p  < 0.01). The post‐wash sperm concentration and total motile sperm count were significantly improved with a longer LEA in the normozoospermic cohort ( p  < 0.05). Discussion and conclusion: Considering the findings in this study and existing literature, a generalized recommendation for long LEA has no clinical value. The LEA should be individualized based on the ejaculate profile and the need for specific clinical intervention.